Role of in-situ and ex-situ livelihood strategies for flood risk reduction: Evidence from the Mayurakshi River Basin, India. (15th February 2022) - Islam, Aznarul; Ghosh, Susmita; Barman, Suman Deb; Nandy, Sweety; Sarkar, Biplab
Abstract: The present study embraces the approach of 'living with flood' for strengthening the community resilience against flood hazards. However, studies in this direction are rare in the Mayurakshi River Basin (MRB). Therefore, the present study has been executed over 2382 sample households spreading over 43 villages distributed in 5 community development blocks in the MRB to reveal the nature of flood hazard and socio-economic vulnerability based on the structured and unstructured questionnaire survey coupled with some secondary data. Flood frequency, depth, duration, and inundation area mapping was done using geospatial techniques to portray the magnitude of hazard while crop diversification index, occupation diversification index, income and expenditure analysis, poverty indices, index of simple multiplier were used to depict the economic vulnerability. The results portray that the lower stretch of the MRB experiences floods every year with one big flood in a decade that inundates 80% of the study area causing huge crop damage and paralyzing the agro-based village economy. Thus, the present study proposes two in-situ models (flood resilient agriculture and fishing in wetlands) and one ex-situ model of international labour migration. The flood resilient agriculture model stresses the introduction of flood-tolerant species and floriculture to secure higher revenue. Similarly, commercial fishing in the wetlands shows also higher income potential. Moreover, the model of labour migration has proved how the strengthening of the economy could be achieved through an economic multiplier. The models will be helpful for inclusive decision making. Graphical abstract: Image 1 Highlights: Flood hazard and community vulnerability of the Mayurakshi River Basin are addressed using geospatial and field data. The agrarian economy has been pushed back to a marginalized condition due to recurrent floods. Occupational transformations and increasing international labour migration are vividly observed in flood-prone areas. Two in-situ and one ex-situ livelihood strategies are proposed to better live with the floods.